Penggunaan Teknologi Informasi (IBS Collect) Terhadap KepuasanNasabah Pada Lembaga Perkreditan Desa (LPD) Desa Adat Celuk - Putu Pande Yudiastra; Ni Luh Gede Putu Purnawati; Gusti Ngurah Mega Nata (Jurnal Ilmiah Satyagraha, 2024)
The aim of this research is to find outThe influence of IBS (IntegratedMicro Banking System) technology services on customer satisfaction at LPDCeluk Sukawati, Gianyar. The research method in this study used a questionnairedistributed to 100 customers from LPD Celuk Sukawati, Gianyar. The analysistechnique used is simple linear regression analysis. Based on the results of theanalysis, it was found that the influence of IBS (Integrated Micro Banking System)technology services on customer satisfaction at LPD Celuk Sukawati, Gianyarwas positive and significant for customer satisfaction at LPD Celuk SukawatiGianyar. This is based on a regression coefficient of 0.838 with a determinationof 74.4%, which means that the influence of IBS (Integrated Micro BankingSystem) technology services has an effect of 74.4% on customer satisfaction atLPD Celuk Sukawati, Gianyar, while the remaining 26.6% was influenced byother variables which were not examined in this study. Apart from that, with the ttest, the calculated t-value is obtained16.893 with a significance value of 0.000,because the significance value of 0.000 is smaller than 0.05, meaning there is apositive and significant influenceIBS (Integrated Micro Banking System)technology services on customer satisfaction at LPD Celuk Sukawati, Gianyar